Characterization of the azo reductase activity in a novel ascomycete yeast strain - Ramalho, Patrícia Alexandra Costa Ferreira (2002)
Poster apresentado no XIII Congresso Nacional de Bioquímica, Lisboa, 5-7 Dezembro 2002.